2019
DOI: 10.22605/rrh5206
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the challenges of caring for a child with foetal alcohol spectrum disorder: a Pilbara community perspective

Abstract: addition to caregivers having awareness of the complexities impacting the children's biological families. Conclusion:The caregivers in this study have gained valuable knowledge and wisdom through caring for a child with FASD that can benefit health professionals and the broader community. Whilst the caregivers in this study have overcome challenges through developing and adapting their own strategies, support services providing tailored programs for caregivers when they first start caring for a child with FASD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In several studies, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] adoptive and biological caregivers described using adaptive parenting styles to support individuals with FASD. Specifically, biological and adoptive caregivers reported that maintaining structure and routine are key.…”
Section: Caregivers Use An Adaptive Parenting Style To Support the In...mentioning
confidence: 99%
See 3 more Smart Citations
“…In several studies, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] adoptive and biological caregivers described using adaptive parenting styles to support individuals with FASD. Specifically, biological and adoptive caregivers reported that maintaining structure and routine are key.…”
Section: Caregivers Use An Adaptive Parenting Style To Support the In...mentioning
confidence: 99%
“…Motivation to foster children with FASD Foster parents choose to foster children with FASD to support the child and to develop their own parenting skills. 47 Benefits of respite care but concerns Respite care is useful to give caregivers a break and can help manage difficult behaviours; 22,24,36,46 however, some caregivers are hesitant to use it because of the risk to the child. 24 Professional strategies to support individuals with FASD Professionals use several strategies to support individuals with FASD:…”
Section: Subtheme Description Of the Subthemementioning
confidence: 99%
See 2 more Smart Citations